Tecendo a vida sob braços fortes: caracterização da violência contra mulheres na cidade de São Gabriel da Cachoeira/AM - Melo, Flávia (2023)
This report is born out of a collective effort to respond to the constant complaints of women leaders of the Department of Indigenous Women of the Federation of Indigenous Organizations of Rio Negro (FOIRN) regarding the violence that afflicts them in São Gabriel da Cachoeira/AM, the "most indigenous people of Brazil". For some years now, a series of initiatives have been developed through a partnership between the Observatório da Violência de Gender in Amazonas of the Federal University of Amazonas, the Collective for Research in Anthropology, Art and Public Health of the University of São Paulo, the Department of Indigenous Women of Rio Negro from FOIRN and Instituto Socioambiental to better understand the problem and build collective paths for mitigation and prevention. This collective enterprise has sought to learn more and better understand the forms of violence with which indigenous women from Rio Negro are socially obliged to deal with in their life paths, especially in the city of São Gabriel da Cachoeira; as well as learning more about how these women and their networks deal with these aggressions, conflicts and violence.